Complete resection of a huge parapharyngeal lesion without neurovascular injuries poses a big challenge. Issue 4 (22nd April 2021) - Hammed, Ali; Alassaf, Areeg; Hammed, Salah; Issa, Hala
ABSTRACT: Pleomorphic adenoma is the most common salivary gland neoplasm, accounting for 63% of all parotid gland tumors. Most tumors originate in the superficial lobe but, more rarely, these tumors may involve the deep lobe of the parotid gland, growing medially and occupying the parapharyngeal space (PPS). Our case presents a 48-year-old man with an extremely huge recurrent parapharyngeal lesion that bulging in the nasopharynx and the oropharynx and significantly comprised the airways. Surgery was planned to approach the deeper lobe of parotid gland and para-pharyngeal mass by transparotid, transmandibular swing approach. Histopathological examination revealed the features suggestive of pleomorphic adenoma. The patient was discharged after 9 days with no facial nerve deficit. Management of these tumors is more challenging due to the anatomical location of the para-pharyngeal space. Preoperative definitive diagnosis, with tumor typing, is less important, and incisional biopsy of any PPS mass should definitely be avoided, in order not to run the risk of a significantly higher rate of recurrence.